2017
DOI: 10.28991/cej-2017-00000077
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Precast Concrete Curbs Using Rubber and Nano Material

Abstract: Disposal of waste tire rubber has become one of the major environmental issues in each part the World. One of the possible solutions to dispose of scrap tire rubber is using them into concrete curbs. This paper presents a new method to ameliorate the rubber concrete using a particular rubber size and Nano Material. Initially six mix designs were performed to determine the optimized size and percentage of rubber according to compressive strength. Afterwards, the major concrete curbs were made with the optimum m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Since the flexural properties of concrete are important for kerbs, especially when constructed on reactive soils, rubberized concrete can be a potential solution in such scenarios. Some researchers already used TDA in kerb application and found it desirable, e.g., Komaki et al [89], Munikanan et al [90] and Johari et al [91].…”
Section: Recycled Concretementioning
confidence: 99%
See 1 more Smart Citation
“…Since the flexural properties of concrete are important for kerbs, especially when constructed on reactive soils, rubberized concrete can be a potential solution in such scenarios. Some researchers already used TDA in kerb application and found it desirable, e.g., Komaki et al [89], Munikanan et al [90] and Johari et al [91].…”
Section: Recycled Concretementioning
confidence: 99%
“…It is to be noted that for different kerb materials (concrete, stone and polymer), even for the same property, the testing procedure applicable may be different; for example, a testing method applicable for concrete may not be particularly applicable to polymer or stone, and caution should be exercised while interpreting values and comparison presented in Table 4. Recycled Concrete Slightly lower than NC [75] Flexural strength slightly lower than NC [75] Slightly less than NC [94] Lower than NC [95] Less than NC [96] Slightly higher than NC [75] Slightly lower than NC [75] Rubberized Concrete Lower than NC [97] Higher deflection tolerance than NC [85] Higher than NC [81] Higher than NC [89] Improved than NC [89] Lower than NC [89] Slightly lower than NC [97] Sandstone 25-100 [ Recycled Plastic -Higher deflection tolerance than NC [3] Higher than NC…”
Section: Stonementioning
confidence: 99%
“…e comparative study on the flexural behavior of rubberized reinforced concrete beams conducted by Alasmari et al revealed an ameliorated performance with the use of the hybrid beams [19]. e effect of using waste tire rubber and nanomaterial in the construction of concrete curbs has been studied by Komaki et al e results showed a positive effect on durability and abrasion resistance [20]. In this research study, hybrid silicone rubber concrete (HSRC) properties using mechanical tests on the different percent of liquid silicone rubber to the total mineral aggregate's volume in concrete at different ages are investigated.…”
Section: Introductionmentioning
confidence: 99%